ONTOLOGICAL PROBLEMS OF THE PHILOSOPHY OF ECONOMICS (Modern education and development, 2025)
This article delves into the ontological foundations of economic being, situating it within the broader philosophical inquiry into the nature of existence. Two contrasting perspectives frame the analysis: being as a primordial, unchanging element and being as the totality of all that exists, capable of becoming and development. Adopting the latter view, the study explores the systemic interconnections among natural, social, and ideal being, emphasizing the pivotal role of economic being in social life. Through a materialist framework informed by Marxist principles—materialism, interdependence, development, and the existence of objective laws—the article argues that labor constitutes the social substance underpinning economic being across its historical manifestations. Addressing fundamental questions about existence, relationships, and processes of becoming, this work offers a dialectical understanding of economic being’s foundational significance, engaging with critiques from Durkheim, Weber, and others to refine its conclusions.